Identification of supplier-induced demand: What kind of consumer information matters? - Christian Schmid (University of Bern, Department of Economics, 2013)
The focus of the present study is on consumer health information in relation to supplier induced demand (SID). We argue that a comparison between medical professionals and nonmedical professionals fails to identify demand inducement. Using a new information measure based on questions of the Swiss Health Survey, we estimate a Poisson hurdle model for office visits and the length of stay in hospitals. We find that information has a negative effect on health care utilization. Consequently, we find evidence for SID while our findings support the argument that the profession cannot be used to identify demand inducement.
Keywords: I11; I18; C24; 330; Supplier-Induced Demand; Consumer Information; Poisson-Hurdle Model; Gesundheit; Konsumentenverhalten; Asymmetrische Information; Angebot; Krankenhaus; Statistische Verteilung; Schweiz